1990
DOI: 10.1002/nur.4770130304
|View full text |Cite
|
Sign up to set email alerts
|

Social support for women during chronic illness: The relationship among sources and types to adjustment

Abstract: The purpose of this study was to explore who in the network provided what type of support in relation to psychosocial adjustment for women experiencing chronic illness. The Norbeck Social Support Questionnaire was administered to 125 chronically ill women, along with measures of depression (CES-D), family illness demands (Demands of Illness Inventory), marital quality (Spanier Dyadic Adjustment Scale), and family functioning (FACES-II). Repeated-measures ANOVA was used to examine the average amount of support … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
2
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(141 citation statements)
references
References 26 publications
6
127
2
6
Order By: Relevance
“…The contact with children might be of a different quality as compared to that with friends or neighbours. Studies on network structure focusing on who is providing support revealed stronger effects for help provided by relatives and spouses as compared to friends (Dean et al 1990;Primomo et al 1990). Dean et al (1990) examined differences in the effects of functional expressive support by source on depressive symptoms and found that spouse, friends, and adult children were found to rank in descending order of importance.…”
Section: Determinants Of Mental Healthmentioning
confidence: 99%
“…The contact with children might be of a different quality as compared to that with friends or neighbours. Studies on network structure focusing on who is providing support revealed stronger effects for help provided by relatives and spouses as compared to friends (Dean et al 1990;Primomo et al 1990). Dean et al (1990) examined differences in the effects of functional expressive support by source on depressive symptoms and found that spouse, friends, and adult children were found to rank in descending order of importance.…”
Section: Determinants Of Mental Healthmentioning
confidence: 99%
“…Social support enhances psychological adjustment, 39 decreases depression, anxiety, and illness demands, and increases quality of life. 10 In this study, a significant correlation was found between social support and anxiety, indicating that the higher the level of social support, the lower the patient's anxiety score.…”
Section: Anxiety and Hemodialysismentioning
confidence: 99%
“…There are many studies in which better illness adaptation and HRQoL have been related to greater family support and/or less family conflict (11)(12)(13)(14)(15). The influence of marital support has been shown to be significant for couples coping with other illnesses (16,17) and similarly may be particularly significant for couples in which one partner has diabetes, as the diabetes care regimen (e.g., food purchase and preparation, medication administration, and exercise involvement) often involves the spouse (16).…”
mentioning
confidence: 99%